Pemberian Asimilasi Terhadap Warga Binaan di Lembaga Pemasyarakatan Kelas IIA Permisan Nusakambangan - Miskiah, Siti; Agung Perdana, Nino; Yusri Annur, Ghinia (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2025)
This study examines the effectiveness of granting assimilation to inmates at the Class IIA Permisan Correctional Facility, Nusakambangan. Assimilation is one of the inmates’ rights aimed at supporting the correctional process and facilitating social reintegration. However, its implementation often encounters several challenges, including regulatory issues, limited human resources, and social stigma. The main problems discussed are the effectiveness of assimilation in the Permisan Correctional Facility in terms of its conformity with existing legal regulations, as well as the supporting and inhibiting factors that influence its implementation. This research employs a qualitative approach using literature review and descriptive analysis. Data were obtained from statutory regulations, official reports, and secondary sources such as previous studies. The findings indicate that the implementation of assimilation generally complies with regulations, but its effectiveness has not been fully optimal. Contributing factors include limited human resources, negative public perceptions of ex-inmates, and security considerations within the correctional institution. On the other hand, supporting factors consist of clear regulatory frameworks, structured correctional programs, and the commitment of correctional officers in carrying out the policy.This study is expected to provide academic contributions to the development of correctional studies and serve as practical input for correctional institutions in improving the quality of inmate rehabilitation through assimilation programs. Keywords: Assimilation, Permisan Correctional Facility, Nusakambangan, Inmates